2019
DOI: 10.1152/ajpendo.00548.2018
|View full text |Cite
|
Sign up to set email alerts
|

Liver X receptor-α activation enhances cholesterol secretion in lactating mammary epithelium

Abstract: Liver X receptors (LXRs) are ligand-dependent transcription factors activated by cholesterol metabolites. These receptors induce a suite of target genes required for de novo synthesis of triglycerides and cholesterol transport in many tissues. Two different isoforms, LXRα and LXRβ, have been well characterized in liver, adipocytes, macrophages, and intestinal epithelium among others, but their contribution to cholesterol and fatty acid efflux in the lactating mammary epithelium is poorly understood. We hypothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 59 publications
2
4
0
Order By: Relevance
“…LXR α has been shown to promote lipid synthesis in mammary gland by regulating the expression of multiple genes during the process of milk fat synthesis in buffalo and cattle, especially through the regulation of LXRE site in the core promoter region of its target genes 10 , 27 . Consistent with previous reports of increased expression levels of LXRα in murine mammary epithelial cells and bovine mammary gland tissues from non-lactation to lactation 28 , 29 , this study showed that the mRNA abundance of the three LXRα transcripts of buffalo in lactation stage were all significantly higher than those in the non-lactation period, indicating that LXR α is an important regulator of milk fat synthesis, which is also consistent with previous finding 10 . Notably, although there was a significant difference in the expression of LXRα2 and LXRα3 between lactation and non-lactation, the magnitude of the difference is very small.…”
Section: Discussionsupporting
confidence: 92%
“…LXR α has been shown to promote lipid synthesis in mammary gland by regulating the expression of multiple genes during the process of milk fat synthesis in buffalo and cattle, especially through the regulation of LXRE site in the core promoter region of its target genes 10 , 27 . Consistent with previous reports of increased expression levels of LXRα in murine mammary epithelial cells and bovine mammary gland tissues from non-lactation to lactation 28 , 29 , this study showed that the mRNA abundance of the three LXRα transcripts of buffalo in lactation stage were all significantly higher than those in the non-lactation period, indicating that LXR α is an important regulator of milk fat synthesis, which is also consistent with previous finding 10 . Notably, although there was a significant difference in the expression of LXRα2 and LXRα3 between lactation and non-lactation, the magnitude of the difference is very small.…”
Section: Discussionsupporting
confidence: 92%
“…1A). These findings are consistent with published data showing that the Ret gene is most highly expressed in lactating mammary glands (Bambhroliya et al, 2018;Clarkson et al, 2004;Grinman et al, 2019;Stein et al, 2004). Analysis of mammary tissue lysates by WB revealed that lactating exhibit high levels of active RET protein (phosphorylated RET) compared to glands from post-lactating animals (Fig.…”
Section: Ret Expression Is Regulated During Mammary Gland Developmentsupporting
confidence: 93%
“…Still, LXR/RXR activation was already identified as a player in human granulosa cells as well as in follicular fluid 37,68 . The system contributes to cholesterol homeostasis and lipid metabolism in many tissues 69 . Cholesterol is an important compound with a role as membrane component or precursor in steroid hormone production and lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%